CORRELATION OF DEGREE OF LUMBAR SPINAL CANAL STENOSIS BASED ON LEE CLASSIFICATION AND SCHIZAS CLASSIFICATION USING LUMBOSACRAL MRI TO OSWETRY DISABILITY INDEX (ODI) IN LOW BACK PAIN PATIENTS. - Samban, Ida; Baan, Junus; Rauf, Rafikah; Zainuddin, Andi Alfian; Kaelan, Cahyono; Ilyas, Muhammad (E-Jurnal Medika Udayana, 2024)
The Lumbar spinal canal stenosis is one of the most common problems found representing the spine degenerative disease in the elderly population. Its prevalence is 5 out of 1000 people over the age of 50 years. The magnetic resonance imaging (MRI) examination is the gold standard in confirming the diagnosis of the lumbar spinal stenosis. The Oswetry Disability Index (ODI) is a questionnaire to assess the disability in the Low Back Pain (LBP) patients. The research aims at investigating the correlation between the degree of lumbar spinal canal stenosis based on Lee and Schizas's classification of ODI in LBP patients. This was the prospective research. The data were obtained through the PACS computer of Dr Wahidin Sudirohusodo Hospital Makassar and ODI questionnaire interview. The research results indicates that of 73 patients suffering from lumbar spinal canal stenosis, most of them are females comprising 41 people (56.2%). The most frequent age groups are 46-55 and 56-65 years old with 24 people (32.9%) in each group. The highest Body Mass Index (BMI) was Obesity I, 25 people (34.2%). The most commonly affected disc level is L4-L5 52 people (71.2%). The conclusion of the research is that there is the significant correlation between the degree of the lumbar spinal canal stenosis of Lee’s classification (p<0.001, r = 0.960) and Schizas’s classification (p<0.001, r = 0.948) with ODI. The higher the degree of lumbar spinal canal stenosis, the higher the patient's disability will be. Keywords:Low Back Pain (LBP), Lumbar spinal canal stenosis, Magnetic Resonance imaging (MRI), Schizas’s classification, Lee’s classification, Oswetry Disability Index (ODI)